Proposal for Human Respiratory Syncytial Virus Nomenclature below the Species Level - Salimi, Vahid; Viegas, Mariana; Trento, Alfonsina; Agoti, Charles N.; Anderson, Larry J.; Avadhanula, Vasanthi; Bahl, Justin; Bont, Louis; Brister, J. Rodney; Cane, Patricia A.; Galiano, Mónica; Graham, Barney S.; et al. (Emerging infectious diseases, 2021)
Human respiratory syncytial virus (HRSV) is the leading viral cause of serious pediatric respiratory disease, and lifelong reinfections are common. Its 2 major subgroups, A and B, exhibit some antigenic variability, enabling HRSV to circulate annually. Globally, research has increased the number of HRSV genomic sequences available. To ensure accurate molecular epidemiology analyses, we propose a uniform nomenclature for HRSV-positive samples and isolates, and HRSV sequences, namely: HRSV/subgroup identifier/geographic identifier/unique sequence identifier/year of sampling. We also propose a template for submitting associated metadata. Universal nomenclature would help researchers retrieve and analyze sequence data to better understand the evolution of this virus.